ANALISIS STRATEGI PELAYANAN KANTOR PERTANAHAN KABUPATEN MAGELANG PASCA PANDEMI COVID - 19 - Muchamad Habibu Lukman; Shinta Ratnawati (STIMI Handayani Denpasar, 2021)
The emergence of the Covid-19 Pandemic gave a significant impact on world change. Starting from the social aspects, economic aspects, to daily life, there is almost no sector that is not affected by the emergence of the Covid-19 Virus, including public services. The government limited social relations that exist in the community, encouraging most of the Government employees to work at home, which results in the public service sector unable to run normally as usual. All public service providers including the Agency Land Office sector Magelang must implemented a new service strategy in accordance with health protocols so that service sustainability is maintained. This research is a qualitative descriptive study used interview date, observation, and literature review. The results of the SWOT analysis show that the Agency Land Office sector Magelang must make system changes and maintain optimal service quality. This can be done by implementing a strategy to changes service policies in accordance with the functions of the Land Agency and meeting the technical requirements of health protocols.